Judicialisation of politics and Kenya's 2017 elections. Issue 2 (3rd April 2019) - Kanyinga, Karuti; Odote, Collins
ABSTRACT: Kenya's 2017 elections stand out as the most litigated and judicialised in the country's electoral history. The election witnessed a litany of legal disputes over rules and regulations ahead of the polls, two presidential petitions, and 388 petitions for other seats. Rulings met with controversy as losers viciously attacked the courts. Every decision the courts made potentially caused them trouble; it raised the ire of either the government or the opposition. Nevertheless, the judiciary made decisions independent of any party and candidate, and played such a critical role in the elections that it ultimately overshadowed the Independent Electoral and Boundaries Commission (IEBC). This article reveals how the judicialisation of elections in Kenya is an outcome of the 2010 Constitution, which sought to moderate the country's 'winner-takes-all' politics. We argue that the electoral process in Kenya will remain judicialised not only because the courts have gained a degree of independence and can make brave decisions, but also that the political culture has not changed: the judiciary operates in an environment in which partisan political interests weaken all institutions and in which politicians seek to use the courts to advance their interests.